Tax Smoothing in a Financially Repressed Economy : Evidence from India - Cashin, Paul (IMF Working Papers; Working Paper ;, 1998)
India has a long history of running fiscal deficits. Two broad considerations motivate a government to run a deficit: tax smoothing and tax tilting. This paper tests a version of Barro's tax-smoothing model, using Indian data for the period 1951-52 to 1996-97. The empirical results indicate that the central government of India has tax-smoothed, while the regional governments of India have not. The paper also finds evidence of tax tilting, reflected in financial repression, which has led to the accumulation of excessive public liabilities.